2012
DOI: 10.1098/rspb.2012.0445
|View full text |Cite
|
Sign up to set email alerts
|

Historical pesticide applications coincided with an altered diet of aerially foraging insectivorous chimney swifts

Abstract: Numerous environmental pressures have precipitated long-term population reductions of many insect species. Population declines in aerially foraging insectivorous birds have also been detected, but the cause remains unknown partly because of a dearth of long-term monitoring data on avian diets. Chimney swifts (Chaetura pelagica) are a model aerial insectivore to fill such information gaps because their roosting behaviour makes them easy to sample in large numbers over long time periods. We report a 48-year-long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 50 publications
4
74
0
1
Order By: Relevance
“…Because of the diversity and geographical distance between the wintering ranges of species in this ecological guild, it could be argued that factors in these ranges are unlikely to simultaneously affect these species, while forces affecting arthropod populations in their breeding range (e.g. AI and changing agricultural practices) are more likely to explain this guild-wide decline [5]. Nevertheless, in UK-breeding birds, breeding habitat (farmland versus wood) was a very strong predictor of historical declines in the 1970s and 1980s but did not explain more recent demographic trends [60], whereas current declines of migrant birds breeding in Europe are best explained by characteristics of wintering habitats [61].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the diversity and geographical distance between the wintering ranges of species in this ecological guild, it could be argued that factors in these ranges are unlikely to simultaneously affect these species, while forces affecting arthropod populations in their breeding range (e.g. AI and changing agricultural practices) are more likely to explain this guild-wide decline [5]. Nevertheless, in UK-breeding birds, breeding habitat (farmland versus wood) was a very strong predictor of historical declines in the 1970s and 1980s but did not explain more recent demographic trends [60], whereas current declines of migrant birds breeding in Europe are best explained by characteristics of wintering habitats [61].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, aerial insectivores, which comprise several farmland species, are often regarded as the most steeply declining bird guild in industrialized countries [3], particularly in northeastern North America [4]. While the reasons for this decline remain largely speculative, insectivory is a life-history trait shared by all species in this otherwise ecologically diverse guild, suggesting their decline is related to a parallel widespread decline in insect abundances [4,5]. Numerous studies have shown that agricultural intensification, most likely through habitat homogenization and pesticide use, negatively impacts insect diversity and abundance in agricultural landscapes [6,7], constraining farmland aerial insectivores to breed in depauperate habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Overuse of various nondegradable agrochemicals has been suggested as one of the principal reasons for the population decline of seven of the eight EV species examined: bald eagle [38], white-tailed eagle [39], kea [40], Adele penguin [41], emperor penguin [42], chimney swift [43], and the Dalmatian pelican [44]. To investigate whether agrochemical use also contributed to the decline of the crested ibis survival, we first examined the relevant historical evidence.…”
Section: Historic Agrochemical Overuse and Relevant Mutated Genes In mentioning
confidence: 99%
“…Climate change is also expected to disproportionately affect populations in more seasonal habitats due to a phenological mismatch between food availability and timing of breeding in long-distance migrants [21]. Agricultural pesticide use may also influence aerial insectivore populations, through broad changes in their prey base [22]. Nebel et al [20] suggested that northern populations may face higher mortality on the wintering grounds due to agricultural pesticides in South America, either through direct mortality or indirectly via reduction in food availability [23].…”
Section: Introductionmentioning
confidence: 99%